1997
DOI: 10.1007/s002770050270
|View full text |Cite
|
Sign up to set email alerts
|

Familial Hodgkin's disease: a disease of young adulthood?

Abstract: Familial Hodgkin's disease (FHD) is estimated to represent approximately 4.5% of all cases of Hodgkin's disease (HD). Shared environmental factors, such as Epstein-Barr virus and other viral agents, and genetic determinants have all been proposed to explain familial aggregation of HD. In order to compare the characteristic features of FHD with those of the much more common sporadic form, we reviewed 28 articles on FHD, published between 1972 and 1995, and analyzed in further detail data from 18 papers, reporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 24 publications
1
21
0
3
Order By: Relevance
“…The highly selected families in our sample are not representative of HL in the population. Consistent with clinical descriptions of familial HL in the literature, 43 referrals to our group are mostly families with cases that have early onset and NS subtype. There are a few later onset cases in these families, but even these are found within families having early onset in other members.…”
Section: Discussionsupporting
confidence: 83%
“…The highly selected families in our sample are not representative of HL in the population. Consistent with clinical descriptions of familial HL in the literature, 43 referrals to our group are mostly families with cases that have early onset and NS subtype. There are a few later onset cases in these families, but even these are found within families having early onset in other members.…”
Section: Discussionsupporting
confidence: 83%
“…Some investigators estimate the incidence of familial Hodgkin's lymphoma to be *4.5% [42]. Hodgkin's lymphoma may occur in familial clusters more frequently than non-Hodgkin's lymphoma [35].…”
Section: Discussionmentioning
confidence: 99%
“…20 Association to human leukocyte antigen and linkage to non-human leukocyte antigen loci have been suggested in familial HL, and the genetic susceptibility seems mainly to be related to the disease in young adults. 6,7,[21][22][23] The interaction of genes and environmental determinants, such as viral infections, have also been implicated, but, for example, EBV is detected in the tumor cells of less than one-third of familial HL patients compared with 40% to 50% in sporadic cases. 24,25 In a few families, a variant in KLHDC8B gene resulting in a decreased protein expression has been reported to associate with cHL, a finding awaiting confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 The distribution of different HL subtypes seems to be similar in sporadic and familial cases. 7 A recent genome-wide association study of HL has confirmed the strong relationship between the major histocompatibility complex region and HL risk and identified 3 additional loci to which common risk variants map. 8 Collectively, such loci do not impact significantly on the familial HL risk, and the strong familial clustering in some families suggests the existence of high to moderately penetrant susceptibility.…”
Section: Introductionmentioning
confidence: 99%